Effectiveness of different bases of support during bridge exercises on gluteus maximus muscle activity in healthy subjects. - Kim, Tae-Hyeong; Jeon, In-Cheol (Isokinetics & Exercise Science, 2026)
Background: The gluteus maximus (GM) and biceps femoris (BF) play important roles in maintaining the stability and mobility of the hip joint during various bridge exercises. The bases of support (BOS) during bridge exercises might have different effects on the muscle activities of the lower extremities. Objective: This study aimed to examine the activation of the GM, BF, and multifidus (MF) muscles and the GM/BF and MF/BF ratios during bridge exercises with three different BOS in healthy individuals. Methods: Twenty healthy individuals participated using surface electromyography of the GM, BF, and MF muscles. The participants were asked to perform bridge exercises in a randomized order: conventional bridge exercise (BE), bridge exercise on a Togu (BET), and bridge exercise on a foam roller (BEF). Results: The muscle activation of the GM was significantly different among the three conditions (BE, BET, BEF) (adjusted p-value [Padj] < 0.01). The GM muscle showed higher activity with BEF compared to BE and BET (Padj < 0.01). The BF showed a significant decrease in BET and BEF compared to BE. The ratios of GM/BF and MF/BF showed a significant increase in BEF compared to BE (Padj < 0.01). Conclusion: The BEF is recommended to selectively increase the GM activity and improve the GM/BF and MF/BF ratios.